Addressing Racially Charged Discourse in Adult Education Graduate Courses - Patsy Medina; Karen Mix-Brown (Adult Education Research Conference, 2008)
Data from dialogue journals, audio-taped conversations, and written life narratives of an assistant professor and graduate student reveal that racism has permeated their lives and they continue to confront it in academe.
Keywords: critical race theory; counterstorytelling; classroom discourse